(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2017)
The fall of the Melaka in 1511 saw the emergence and resurgence of Malay Sultanates trying to fill the void left by the empire. Consequently, there was also an increase in encounters between local people and European explorers and traders that stimulated "ethnic formation" in the Straits of Melaka. Sultanates continued to practice customs that shows music as a symbol of Malay identity and civilization and immortalized through court literature. Music became an important tool that mediated the idea of collective identity and the demarcation of social and political boundaries. Based on early Malay court literature and European accounts, this paper discusses the role of court music known as nobat in this process of Malay identity formation amid the quest for cultural, political and economic supremacy among competing Malay Sultanates between the 15th and 17th centuries. Keywords: nobat, court music, Malay identity, literature, Malay Sultanates